Knowledge Management Implementation Utilizing The Daily Exercise For Employee (Deep46) At Bank BNI - abdi Setia Arief Putra; Achmad Fajar Hendarman (UniSadhuGuna Business School, 2023)
In line with the company's vision, where through BNI Corporate University it seeks to create a world-class learning entity, transformation is needed to change the mindset and behavior of BNI people in learning. Currently, the value of implementing knowledge management at BNI is faster, better, cheaper, wider. The application of knowledge management at Bank BNI has an important value in business continuity. The application of knowledge management can accelerate every development of incoming information, create new innovations, and increase the efficiency of business processes at Bank BNI. One of the implementations of knowledge management at Bank BNI is creating a culture of learning and sharing. Of course learning and sharing activities are recognized (recorded), appreciated, and assessed in determining the Tallent Classification of each BNI employee (commonly called BNI Hi-Movers). One of the tools for implementing knowledge management that runs at Bank BNI is BNI DEEP46 (Daily Exercise for Employee Program). Where every day BNI Hi-Movers receive material in the form of a bite-sized learning method and there are quizzes to answer. Every 1 question is recognized as 5 minutes of learning time. In the implementation of BNI DEEP46 it can be seen that the implementation results are not optimal. There are still many BNI Hi-Movers who do not carry out the obligation to carry out BNI DEEP46 work. In the data presented there was a decrease in participants (employees), from 26,885 employees to only 24,611. As of December 2021, the number of employees is 27,085 people. This means that compulsory learning has not met 100% as expected by BNI management. In evaluating the effectiveness of implementing BNI DEEP46, researchers used the APO (Asian Productivity Organization) KM Assessment Tool. The 7 element components will be combined in the form of a questionnaire. The maximum score is 210, and there are 42 questions covering the seven audit areas. There is a maximum possible score of 30 points in each section. Each item can be assigned a rating between 1 (poorly or not at all) and 5 (very well) (very well). Primary data was collected using a questionnaire then SPSS Statistical Software version 26 was used to analyze the data. From the results of the study it can be concluded that the Leadership variable (X1) has no influence on the outcome, and also the People variable (X3) has no influence on the outcome, this is indicated by the sig. 0.521 and 0.234 <0.05 which means that the leadership and people variables have no influence on the outcome. For process, technology, knowledge process and learning variables, they have a positive and significant influence on the outcome, which can be seen from the significance value of each variable <0.05.